A microscopic spatially confined strategy to realize completely reversible self-healing lattice restoration of MoS2 for ultrastable reversible sodium-ion storage. (27th September 2021) - Tian, Wei; Tian, Jin; Lin, Naiming; Liu, Ye; Zeng, Hui; Dang, Shuo; Jiang, Zhongqing; Wang, Zhongde
Abstract : Double-layer carbon-encapsulated MoS2 (C@MoS2 @C) nanocubes were synthesized and used as an anode for ultralong cycling performance sodium-ion batteries, based on a microscopic spatially confined strategy. Abstract : On account of multiple electron exchange reaction processes, transition metal sulfides with high specific capacities are considered as promising electrode materials for sodium-ion batteries. However, their poor electrical conductivity and fragile structure always result in a poor cycling performance and a low rate capability, which hinder their practical applications. Herein, based on a spatially-microscopic-confined strategy, double-layer carbon-encapsulated MoS2 (C@MoS2 @C) nanocubes were synthesized using nitrogen-doped hollow carbon nanocubes as a precursor, and these were used as anode materials. Due to the self-healing capacity of MoS2 during the charging process, the microstructure of MoS2 was effectively restored and the electrode microstructure was stably maintained under ultra-long-term cycling. With these synergistic effects, the C@MoS2 @C anode exhibited a remarkable reversible capacity of 163.9 mA h g −1 after 10 000 cycles even at an ultrahigh current density (10 A g −1 ), with capacity fading as low as 0.004% per cycle. The current findings of the microscopic spatially confined strategy could provide a promising approach for the rational design of high-capacity electrodes.